The relationship of future anxiety with a multidimensional framework of well-being among undergraduate students: optimism and pessimism as mediators - Gülçin Güler Öztekin (BMC Psychology)
Abstract Background Enhancing and maintaining well-being is of great importance for university students to improve their future lives. Therefore, determining the factors that promote well-being is essential. This study aimed to examine the mediating roles of optimism and pessimism in the association between future anxiety and well-being after controlling gender, age, faculty, and department. Methods 1024 undergraduate students participated in the study. The mean age of students was 20.27 years (SD = 2.02). Preliminary analyses were conducted to determine descriptive statistics, Cronbach’s alpha coefficients, normality, and correlation coefficients between study variables. Mediation analyses were performed to investigate the mediating roles of optimism and pessimism in the association between future anxiety and well-being. Results The results of the study showed that future anxiety was positively associated with pessimism, and negatively associated with optimism, positive emotions, engagement, positive relationships, meaning and accomplishment. Optimism had a positive relationship with the constructs of well-being model, and pessimism had a negative relationship with the pillars of well-being. Optimism and pessimism served as mediators in the link between future anxiety and well-being. Conclusion The findings of this study indicate that students who are anxious about the future are less optimistic and more pessimistic, which in turn leads to lower well-being. The current study suggests that future-oriented thinking and individual strengths, including optimism, should be incorporated into the mental health management of university administrations to promote the well-being of university students.